2021
DOI: 10.1016/j.fertnstert.2020.11.020
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression profiles in the seminal plasma of nonobstructive azoospermia patients with different histopathologic patterns

Abstract: Objective: To investigate microRNA (miRNA) expression profiles in the seminal plasma of nonobstructive azoospermia (NOA) patients with different histopathologic patterns and evaluate potential noninvasive diagnostic biomarkers of NOA. Design: Sequencing and validation using quantitative reverse transcription polymerase chain reaction (qRT-PCR). Setting: Reproductive center and research institute. Patient(s): Thirteen patients with NOA (7 Sertoli cell-only syndrome [SCOS] and 6 hypospermatogenesis to spermatoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 61 publications
1
26
0
Order By: Relevance
“…In the current study, Zhang et al (4) show decreased expression of seminal plasma miR-34c-5p in men with NOA compared with that in fertile controls using high-throughput sequencing. The relative expression of miR-34c-5p is significantly lower in patients with Sertoli-cell-only syndrome than in men with spermatogenesis arrest.…”
supporting
confidence: 50%
“…In the current study, Zhang et al (4) show decreased expression of seminal plasma miR-34c-5p in men with NOA compared with that in fertile controls using high-throughput sequencing. The relative expression of miR-34c-5p is significantly lower in patients with Sertoli-cell-only syndrome than in men with spermatogenesis arrest.…”
supporting
confidence: 50%
“…However, they realized that this alteration in the expression of miR‐34c‐5p was also lower in SCOS cases than in SA cases. These findings suggest that miR‐34c‐5p as a non‐invasive biomarker can distinguish different patterns in non‐obstructive azoospermia (Zhang, Zhang, et al, 2021). Another recent paper has reported that the expression levels of miR‐122‐5p, miR‐34c‐5p, miR‐509‐3‐5p, miR‐449a and miR‐202‐5p decreased in azoospermic patients compared with normal men.…”
Section: Resultsmentioning
confidence: 92%
“…Non‐obstructive azoospermia mainly consists of two histopathologic patterns: Sertoli cell‐only syndrome (SCOS) and spermatogenesis arrest (SA) defect. In a related study, a total of 20 different seminal plasma samples were isolated and purified from seminal plasma by the miRNeasy Micro Kit (Qiagen), and a significant down‐regulation of miR‐34c‐5p was found in seminal plasma samples of patients with non‐obstructive azoospermia compared with normal fertile controls (Zhang, Zhang, et al, 2021). However, they realized that this alteration in the expression of miR‐34c‐5p was also lower in SCOS cases than in SA cases.…”
Section: Resultsmentioning
confidence: 99%
“…Seminal plasma, which is partly derived from epididymal fluid, generates sncRNA profiles that implicate seminal plasma quality in and male fertility. miRNA profiles in seminal plasma are correlated with specific spermatogenic defects and, more broadly, in male infertility [ 217 , 218 , 219 ]. Effects of environmental exposures on spermatogenesis, such as heat stress, may also be reflected by the miRNA profile of seminal plasma [ 220 ].…”
Section: Sncrnas In Sperm Seminal Plasma Follicular Fluid and Embryo Culture Medium As Biomarkers For Fertility And Embryo Development Pomentioning
confidence: 99%